2017
DOI: 10.18632/oncotarget.16779
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-27a sensitizes colorectal cancer stem cells to TRAIL by promoting the formation of Apaf-1-caspase-9 complex

Abstract: MicroRNAs have been proved to participate in multiple biological processes in cancers. For developing resistance to cytotoxic drug, cancer cells, especially the cancer stem cells, usually change their microRNA expression profile to survive in hostile environments. In the present study, we found that expression of microRNA-27a was increased in colorectal cancer stem cells. High level of microRNA-27a was indicated to induce the resistance to TNF-related apoptosis-inducing ligand (TRAIL). Knockdown of microRNA-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…However, transfection with TAZ plasmid reduced the collapse of mitochondria in cisplatin and miR-26b co-treated PC9/R and A549/R cells ( Figure 5A). As the results of mitochondria collapse, we next found that overexpression of miR-26b obviously increased the release of cytochrome c which is a mitochondria-derived and key apoptotic inducer 21 into cytosol of PC9/R and A549/R cells. However, transfection with TAZ plasmid abolished the effect of miR-26b ( Figure 5B).…”
Section: Restoration Of Mir-26b Expression Targets Taz To Increase Thmentioning
confidence: 81%
“…However, transfection with TAZ plasmid reduced the collapse of mitochondria in cisplatin and miR-26b co-treated PC9/R and A549/R cells ( Figure 5A). As the results of mitochondria collapse, we next found that overexpression of miR-26b obviously increased the release of cytochrome c which is a mitochondria-derived and key apoptotic inducer 21 into cytosol of PC9/R and A549/R cells. However, transfection with TAZ plasmid abolished the effect of miR-26b ( Figure 5B).…”
Section: Restoration Of Mir-26b Expression Targets Taz To Increase Thmentioning
confidence: 81%
“…Apaf‐1 is a crucial pro‐apoptotic protein in the mitochondrial apoptosis pathway, with three special structures, of which the caspase recruitment domain (CARD) is the most active. In vertebrates, one of the major mechanisms of caspase activation is to release cytochrome c from mitochondria and then to interact with cell death protein 4 homologue Apaf‐1 (Zhang, Xu, Zhao, & Bai, ). With the assistance of dATP/ATP, caspase binds to cytochrome c, triggers Apaf‐1 oligomerisation, activates procaspase‐3, and further activates caspase‐3 and caspase‐7 (Zhang, Shi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have elaborated the role of miRNAs in regulating the CSC features in the pathogenesis of various human malignancies (Table 1). MiRNA-215 DTL [59] miR-148a WNT, β-catenin [60] miR-199a/b Gsk3β, Wnt/β-catenin-ABCG2 [61] miR-196b-5p STAT3 [62] miRs-31 EphB2 and EphA2 [63] miR-27a Apaf-1/caspase-9 [64] miR-372/373 Nanog, Hedgehog, NFκB, MAPK/Erk, VDR Jak-STAT, TGF-beta, PI3K-Akt, MAPK. [65,66] miR-137 DCLK1 [67] miR-146a β-catenin [68] miR-195-5p STAT3, BIRC5, BCL2, BCL-XL, SOX2, CD133, RBPJ, Notch2 [62,69] Lung miR-128 AKT/ERK, p38, c-met/PI3K/AKT, VEGF/PI3K/AKT, IL-6-JAK-STAT3 [70][71][72][73] miR-181b Notch2 [74] miR-138 TGFβ [75] miR-5100 Rab6 [76] miR-214 c-MYC [76] miR-708-5p Wnt/β-catenin [77] miR-873 miR-125a-3p…”
Section: Role Of Mirna and Oncogenic Signaling Pathways In Human Cancmentioning
confidence: 99%
“…The oncogenic role of dysregulated miR-27a has been well elucidated in a number of human malignancies including CRC via enhanced cell proliferation, invasion and migration, and EMT. In one of the recent studies, it has been found that overexpression of miR-27a in CRC stem cells which is associated with resistance as knocking down of miR-27a sensitizes CRC stem cells towards apoptosis via activation of the Apaf-1/caspase-9 apoptosome-mediated apoptotic pathway [64].…”
Section: Colorectal Cancermentioning
confidence: 99%